Neuromuscular Fatigue in Hamstring and Quadriceps Muscles after Simulated Soccer Match Play and Typical Training Sessions - Massamba, Anasthase; Kouzkouz, Nabil; Geny, Bernard; Favret, Fabrice; Hureau, Thomas J (Medicine and science in sports and exercise, 2025)
This study investigated the mechanisms of neuromuscular fatigue and recovery in quadriceps and hamstring muscles after soccer match play and typical training sessions dedicated to the physical development of players. Fifteen male professional academy soccer players completed at different visits a 90-min simulated soccer match play (MATCH) and four training sessions modulating the metabolic nature (HIIT vs SPRINT) and the mechanical load (number of changes of direction [COD]). Neuromuscular fatigue was evaluated via changes in pre- to postexercise maximal voluntary contraction (MVC), potentiated twitch force (P Tw , peripheral fatigue), and voluntary activation (VA, central fatigue) evoked by electrical stimulation in quadriceps and hamstring muscles. External load was assessed via GPS units. After MATCH, ΔMVC was similar between quadriceps (-18.3% ± 11.6%) and hamstring (-23.2% ± 10.6%) muscles. However, hamstring muscles displayed greater ΔP Tw (-27.2% ± 25.0% vs -17.2% ± 10.9%) but lower ΔVA (-8.2% ± 14.0% vs -18.1% ± 12.7%) than quadriceps muscles. Quadriceps and hamstring muscles fatigue recovered 24 h postmatch. Increasing the mechanical load (number of COD) increased the magnitude of neuromuscular fatigue in quadriceps but not in hamstring muscles. Modulating the metabolic nature of the session (SPRINT vs HIIT) did not influence neuromuscular fatigue in either muscle group. No correlation was found between ΔMVC and a fatigue index derived from GPS metrics for any muscle groups ( r2 < 0.06, P > 0.38). The magnitude and the etiology of neuromuscular fatigue were modulated by the muscle group investigated and the mechanical load of the exercise task. Moreover, the "fatigue index" derived from GPS metrics is not a valid surrogate of neuromuscular fatigue on the field.